THE USAGE OF "RITATOON" INCREASING MEDIA THE ABILITY OF BASIC NOUN RECOGNIZATION FOR STUDENTS WITH MODERATE INTELLECTUAL DISABILITY - Khairiyah, Karunia Yulinda (JPI (Jurnal Pendidikan Inklusi), 2018)
The purpose of this study is to describe the ability to Recognize basic nouns in the moderate intellectual disability before using the media ritatoon, describes the ability to Recognize basic nouns in moderate intellectual disability after using ritatoon media. The design used in this research is Pre Experimental Design with One Group Pre-test Post-test Design. The research instruments are written tests and performance tests for the pretest and posttest. The analysis technique used is the prerequisite Test using the normality test and homogeneity test that was completed with the help of a computer program SPSS 23.0 for Windows and Anova test